Intra-articular injections in osteo-arthritis : a critical evaluation by clinical physico-chemical and experimental methods - Dall, George (Department of Surgery, 2017)
The therapy of osteo-arthritis is a problem which we have inherited from our forebears. It is a considerable problem; one which affects the community very vitally. The disease produces marked disability which burdens our civic economy. Various methods of therapy have been advocated from time to time such as hydro-therapy, physiotherapy and analgesics of different kinds. This thesis will deal only with the intra-articular injection therapy of osteo-arthritis.